Disseminated cancer cells detected by immunocytology in lymph nodes of NSCLC patients are highly prognostic and undergo parallel molecular evolution - Elsner, Felix; Hoffmann, Martin; Fahrioglu-Yamaci, Rezan; Czyz, Zbigniew; Feliciello, Giancarlo; Mederer, Tobias; Polzer, Bernhard; Treitschke, Steffi; Rümmele, Petra; Weber, Florian; Wiesinger, Hellmuth; Robold, Tobias; et al. (Journal of Pathology, 2022)
In melanoma, immunocytology (IC) after sentinel lymph node disaggregation not only enables better quantification of disseminated cancer cells (DCCs) than routine histopathology (HP) but also provides a unique opportunity to detect, isolate, and analyse these earliest harbingers of metachronous metastasis. Here, we explored lymph node IC in non-small cell lung cancer (NSCLC). For 122 NSCLC patients, 220 lymph nodes (LNs) were split in half and prepared for IC and HP. When both methods were compared, IC identified 22% positive patients as opposed to 4.5% by HP, revealing a much higher sensitivity of IC (p < 0.001). Assessment of all available 2,952 LNs of the same patients by HP uncovered additional patients escaping detection of lymphatic tumour spread by IC alone, consistent with the concept of skip metastasis. A combined lymph node status of IC and complete HP on a larger cohort of patients outperformed all risk factors in multivariable analysis for prognosis (p < 0.001; RR = 2.290; CI 1.407–3.728). Moreover, isolation of DCCs and single-cell molecular characterization revealed that (1) LN-DCCs differ from primary tumours in terms of copy number alterations and selected mutations and (2) critical alterations are acquired during colony formation within LNs. We conclude that LN-IC in NSCLC patients when combined with HP improves diagnostic precision, has the potential to reduce total workload, and facilitates molecular characterization of lymphatically spread cancer cells, which may become key for the selection and development of novel systemic therapies. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2022-10-07
Keywords: disseminated cancer cell; early metastasis; molecular evolution of NSCLC; prognosis